AB0502 EVALUATION OF A NOVEL FAST TRACK PATHWAY FOR GIANT CELL ARTERITIS USING PET IN ADDITION TO TAUS AND TAB FOR EARLY DIAGNOSIS. (2nd June 2020) - Ludwig, D.; Shashidhara, A.; Stavrou, C.; Voo, S.; Reshat, R.; Morris, V.
Abstract : Background: Giant Cell Arteritis (GCA) is a common primary systemic vasculitis (1). Its predilection for the temporal artery can result in permanent visual loss if left untreated. Over 25% of patients have involvement of large vessels, such as the aorta, resulting in an increased risk of aneurysm formation and dissection. (3) Diagnosis of GCA is largely clinical and temporal artery biopsy (TAB) has long been the gold standard for diagnosis. In recent years temporal artery ultrasound (TAUS) has emerged as an effective, non-invasive tool to aid diagnosis. Positron-emission tomography (PET) can also be utilised to detect the presence of large vessel involvement but is currently not used in many centres for diagnostic purposes and requires further standardisation and validation (2). The challenge arises from these investigations losing sensitivity in the days following steroid treatment, meaning that rapid access is key to confirm diagnosis. Objectives: To evaluate the impact of the introduction of a fast track pathway (FTP) on prompt diagnostics and treatment. To improve our understanding of the use of PET at diagnosis and compare this to the gold standard TAB, and to TAUS, in our institution. Methods: Cohort 1: 32 patients, all presenting before FTP implementation, identified from outpatient clinics and referrals to the Rheumatology team. Time taken from steroid initiation to TAUS/TAB was extracted from clinical records. Outcomes for this group included number of years on steroid (steroid burden). Cohort 2: 21 patients all referred after implementation of a new GCA FTP. This group contains all patients referred as query GCA, not just those with positive diagnoses. Time from steroid initiation to TAUS/TAB was recorded. The FTP included the addition of PET imaging within 72 hours. Results: Cohort 1: 20 (63%) patients had TAB and 3 (9%) had TAUS. The average time from starting steroid to investigation was 5.2 days and 2 days respectively. The average steroid burden in patients with no confirmatory test was 11 years. If patients had just a single diagnostic test this value dropped to 3 years. Cohort 2: 11 (52%) had TAB, 10 (48%) had TAUS and 11 (52%) had PET. In positive GCA diagnoses, time from steroid start to investigations was 7.2 days, 1 day and 3.2 days respectively. In patients with a negative diagnosis the time frames were 13 days, 1 day and 1.7 days respectively. Sensitivity for TAB was 45.5% and TAUS 40%. Specificity for TAB and TAUS was 100%. These results are comparable to similar studies (4). PET sensitivity was 63.6% and specificity 100%. Conclusion: Prompt diagnostics, best facilitated through a FTP, can reduce steroid burden in GCA even if only one confirmatory test is available. Patients with a low clinical suspicion of GCA and negative TAUS or a high clinical suspicion and positive TAUS stand little to gain from TAB. These findings summarise the first 6 months of our GCA FTP. Continued evaluation of PET in our FTP is needed to understand its role in diagnosis, particularly in patients at risk of vascular complications. References: [1]Crowson CS, Matteson EL. Contemporary prevalence estimates for giant cell arteritis and polymyalgia rheumatica 2015. Semin Arthritis Rheum. 2017; 47 (2) 253–6 [2]Camellino D, Dejaco C. Should 18 F FDG PET imaging be used in the diagnosis of GCA? Nature Reviews Rheumatology 2019; 15 (7) 388–90 [3]Nuenninghoff DM et al. Incidence and predictors of large-artery complication (aortic aneurysm, aortic dissection, and/or large artery stenosis) in patients with giant cell arteritis: a population-based study over 50 years. Arthritis Rheum 2003; 48:3522-3531 [4]Luqmani, R. et al. The Role of Ultrasound Compared to Biopsy of Temporal Arteries in the Diagnosis and Treatment of Giant Cell Arteritis (TABUL): A Diagnostic Accuracy and Cost-Effectiveness Study. Health Technol Assess 2016; 20 (90) 1-238 Disclosure of Interests: None declared